ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI KAKAO DI DESA TONGOA KECAMATAN PALOLO KABUPATEN SIGI - Jalil K. Gugere; Made Antara; Max Nur Alam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
Cocoa is one of the export commodities from plantation sub-sector which is the leading commodity in Central Sulawesi. This research aimed at determining: (1) the influence of  productive plant number, urea fertilizer, SP36 fertilizer, KCl fertilizer, employees, and plant age on cocoa production in Tongoa village, and (2)the income of cocoa farmingin Tongoa village. This research used a survey method.  Sixty five households were taken as samplesusing a simple random technique. The results showed that: (1) Ftest =43.425 with probability               p = 0.000<0.05 at ɑ = 5% indicating that the independent variables such as number of productive plants (X1), urea (X2), SP36 (X3), KCl (X4), employees (X5), and age of plants (X6) simultaneously had significant influence on the cocoa production in Tongoa village Palolo. The adjusted coefficient of determination (R2) was 0.796 showing that the variation  of cocoa production (Y) can be explained by the independent variablesby 79.9%, while               the remaining 20.1% was explained by other factors that were not included in the model, such as climate, etc. The number of productive plants variable (X1), urea(X2), SP36 fertilizer (X3), KCl (X4), employees (X5), and plant age (X6) were also each partially influence the cocoa production in Tongoa village Palolo significantly at the level of 95% while KCl fertilizerat the level of 90%; and (2) The average revenue of the cocoa farming was  IDR 37,251,938.46/1.74 ha/year equal to IDR 21,409,160.04 /ha/year while the average income of cocoa production was IDR 27,798,502.38/1.74 ha/year equal to IDR 15,976,150.79/ha/year.